Pengaruh sanitasi total dengan kejadian diare pada balita di wilayah kerja Puskesmas Simpang Tiga - Yoana Agnesia (EcoNews, 2022)
Diarrhea is a disease that affects infant mortality, diarrheal disease is an endemic disease and is a potential disease of extraordinary events (KLB) accompanied by death. Many factors are the cause of diarrhea such as malnutrition, behavior and total sanitation. Total sanitation is believed to be an important factor in the incidence of daire in infants. The purpose of this study is to find out the relationship of total sanitation in the household which consists of defecation behavior, hand washing behavior with soap, availability of clean water, availability of trash cans, sewerage to the incidence of diarrhea in infants in the Simpang Tiga Health Center in Pekanbaru . Type of quantitative research with survey method. The number of samples in this study were 70 under-five mothers. Sampling used the purposive sampling method. The measuring instruments used were questionnaires and observation sheets. Analysis used chi-square and linear regression. The results of this study show the most significant variable on the incidence of diarrhea is the behavior of hand washing with soap with p <0.05 OR value 12.98. It is expected that the puskesmas will be more vigorous to socialize, through the movement of handwashing with soap to mothers who have toddlers.